Cranial Rosai-Dorfman disease: a case report and literature review - Lv, JunBo; Hu, JiBo; Xu, Houyun; Yu, Xiping (Frontiers in Oncology, 2024)
Rosai-Dorfman Disease (RDD) is a rare, benign, idiopathic histiocytic proliferative disorder, with its occurrence in the cranial bones being particularly uncommon and prone to misdiagnosis in preoperative radiological examinations. This article reports a case of RDD in the left temporal bone. The radiological presentation of intraosseous RDD includes osteolytic bone destruction, infrequent periosteal reaction, clearly defined tumor margins, and marked uniform enhancement on contrast-enhanced scans. However, these radiological features lack specificity, highlighting the necessity of histopathological examination for a definitive diagnosis, especially for the rarer extranodal subtypes of RDD. Surgical excision of the lesion can lead to favorable therapeutic outcomes.